Sexual abuse in religion - Trzebiatowska, Marta (Palgrave Macmillan, 2025)
1 Religion and Sexual Exploitation -- 2 Sex in Defamation -- 3 Satanic Ritual Abuse -- 4 Ethnic Enclaves: Muslims and Jews -- 5 Catholic Priests and Nuns -- 6 Protestant Pastors -- 7 Gurus -- 8 Religious Communities -- 9 Gender and Abuse -- 10 Does Religion Matter?.